Immediate biomechanical, systemic, and interoceptive effects of myofascial release on the thoracic spine: A randomised controlled trial. Issue 1 (January 2019) - Cathcart, Ellie; McSweeney, Terence; Johnston, Ross; Young, Hayley; Edwards, Darren J.
Abstract: Background: Myofascial release (MFR) is used to restore tissue extensibility of the fascia tissue and is considered to be useful in a number of clinical settings such as low back pain, ankle injuries, fibromyalgia, and headaches. There is, however, despite the popularity of MFR in manual therapy, little consensus on whether it leads to biomechanical, systemic or interoceptive outcomes. Aims: This study aimed to explore the immediate biomechanical (increased elasticity for increased range of motion), systemic (local vs. distal areas of pain threshold) and bodily awareness effects (interoception) of a myofascial release technique on the thoracic spine. Method: Twelve healthy participants took part in this triple-bind, repeated measures, cross-over design study, and were randomised into counterbalanced sequences of three conditions; a control, a sham, and the MFR condition. The outcome measures used were; range of motion (ROM), pain pressure thresholds (PPT), and interoceptive sensitivity (IS) to assess biomechanical, systemic, and interoceptive effects of MFR. Results: There were significant increases in ROM and PPT (both local and distal) post MFR intervention. There was also a positive correlation between baseline interoceptive sensitivity and post-MFR ROM and a negative correlation for baseline interoceptive sensitivity and post-MRF PPT. Interoceptive sensitivity did increase post-MFR but this was non-significant. Conclusions: The increase in ROM suggests that the MFR may have caused a biomechanical change in tissue elasticity creating an increase in tissue flexibility. The increase in both local and distal sites of the PPT suggest an overall systemic response to the therapy. The correlation between baseline IS and post-MFR ROM and PPT suggest that IS may be usefully applied as a predictor for ROM and PPT post-MFR.